Effects of short‐chain fatty acids on Actinomyces naeslundii biofilm formation. (3rd June 2013) - Yoneda, S.; Kawarai, T.; Narisawa, N.; Tuna, E.B.; Sato, N.; Tsugane, T.; Saeki, Y.; Ochiai, K.; Senpuku, H.
Summary: Actinomyces naeslundii is an early colonizer and has important roles in the development of the oral biofilm. Short‐chain fatty acids (SCFA) are secreted extracellularly as a product of metabolism by gram‐negative anaerobes, e.g. Porphyromonas gingivalis and Fusobacterium nucleatum ; and the SCFA may affect biofilm development with interaction between A. naeslundii and gram‐negative bacteria. Our aim was to investigate the effects of SCFA on biofilm formation by A. naeslundii and to determine the mechanism. We used the biofilm formation assay in 96‐well microtiter plates in tryptic soy broth without dextrose and with 0.25% sucrose using safranin stain of the biofilm monitoring 492 nm absorbance. To determine the mechanism by SCFA, the production of chaperones and stress‐response proteins (GrpE and GroEL) in biofilm formation was examined using Western blot fluorescence activity with GrpE and GroEL antibodies. Adding butyric acid (6.25 mm ) 0, 6 and 10 h after beginning culture significantly increased biofilm formation by A. naeslundii, and upregulation was observed at 16 h. Upregulation was also observed using appropriate concentrations of other SCFA. In the upregulated biofilm, production of GrpE and GroEL was higher where membrane‐damaged or dead cells were also observed. The upregulated biofilm was significantly reduced by addition of anti‐GroEL antibody. The data suggest biofilm formation by A. naeslundii was upregulated dependent on the production of stress proteins, and addition of SCFA increased membrane‐damaged or dead cells. Production of GroEL may physically play an important role in biofilm development.